Pengembangan Uji Tetrazolium sebagai Metode Analisis Vigor Benih Botani Bawang Merah - Afifah, Nurul; Widajati, Eny; Palupi, Endah Retno (Jurnal Hortikultura Indonesia, 2020)
The tetrazolium (TZ) test is one of methods to estimate viability and vigor of seed. This study aimed to improve the methodology of vigor analysis of true seed of shallot. In this research, two varieties of shallot seeds were used, those were Trisula and Tuk-tuk. Pre-treatment in the tetrazolium test of shallot seeds was applicated, directly soaking in water for 18 hours. Seed preparation before staining used method: the thoroughly linear side of the seed was cut longitudinally as the only thin slice, and convex side of seed was punctured with a scalpel. Seeds were stained for 18 hours in a 1% tetrazolium solution at 30 oC. Seed patterns classified in four categories were determined. The results were four patterns of high-seedling as criteria for seed vigor, five patterns of low seedling vigor, seven patterns of abnormal seedling, and four patterns of dead seed. Viability and vigor physiological parameters are closely correlated with the results of high seedling vigor patterns. The high seedling vigor patterns had high the correlation coefficients (r) with physiological test parameters in the laboratory including vigor index (r= 0.882), normal seedling dry weight (r= 0.899), and seed growth rate (r= 0.875). It indicated the vigor staining patterns can predict the vigor of seeds.